Fish farming: A net full of information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The flagship of all information on fish farming is the International Center for Living Aquatic Resources Management (ICLARM), which moved from its original headquarters in the Philippines to Malaysia in February 2000. It runs question-and-answer...